The Value of Character Education in the Terbang Papat Music Performance (Study of the Al-Madais Pladen Jekulo Kudus Group) (Catharsis, 2022)
Many paths can be taken to educate someone to have character. One of them is by participating in maintaining traditional Islamic art culture, namely terbangan music (an Islamic musical art) which is expected to foster character education applied in the process of terbang papat performance. Therefore, it is hoped that someone is not only limited to playing his musical instrument and singing his poems, but he/she can understand the character values ​​contained and apply them in everyday life. This study aimed to analyze the value of character education applied in the performance of terbang papat by the Al-Madais music group in the village of Pladen Jekulo Kudus. This research used an interdisciplinary approach with descriptive qualitative research type. Data collection techniques used the method of observation, interviews, and documentation. All data were analyzed by data reduction, presentation, conclusion drawing or verification. The results showed that the value of character education was applied in the process of the terbang papat performance by the Al-Madais music group in the village of Pladen Jekulo Kudus, including: religious values ​​within the sung poetry, tolerance values ​​with mutual respect, discipline values ​​by obeying the rules, work-hard values by practicing earnestly, creative values ​​by cultivating the power of creativity in performing terbang papat, the value of curiosity by increasing knowledge and experience, friendly/communicative values ​​by communicating each other among the terbang papat players, and the value of responsibility to carry out their duties and obligations in working on terbang papat song as well as possible